Pembuatan Prototype Smart Power Strip Berbasis Mobile - Andi Dahroni; Muhammad Fadli Pratama; Eka Putra (KILAT, 2020)
Controlling electrical equipment within a certain time frame is one thing that is quite important. By controlling existing equipment in the house such as air conditioning, TV, fans, etc. It is often found that some electrical tools that survive are not used, in addition to waste also shortens the life of the electrical appliances. Therefore we need control and supervision of electrical devices using intelligent power strips. IoT or commonly known as the internet from things that are concepts that are intended to get the concept of the benefits of internet connectivity that is connected continuously. This concept can be used for monitoring and controlling electrical equipment that connects smart electrical terminals or power strips. By using an electrical terminal device that is paired with a system and module that can be controlled using a smartphone. Android is one of the many smartphone OSes that can bridge or facilitate all human work, one of which is in terms of control, which functions from this android as a remote control media that can be accessed by electronic devices in the home and certainly has connected first with the IoT module. This study discusses making smart sockets or smart power strips that can be rotated using a smartphone so that any electrical equipment can be used on users who do not use home.